Refining pore size, functionality and stability in porous hybrid frameworks - Nevin, Adam C (2017)
This thesis describes the utilisation of a new, facile route for rapid ligand synthesis for the design, synthesis and characterisation of metal-organic frameworks (MOFs), and the subsequent refinement of ligand synthesis to discover a 2-step green alternative synthetic route to an analogous ligand for use in the same. From these ligands, two series of MOFs are detailed; a Cu(II) series with simulated isotherms showing promising CH4 and CO2 high pressure uptake, and two Zr(IV) MOFs with enhanced stability and their measured high pressure isotherms. Chapter 1 introduces the need for highly functional materials to answer the needs of current energy production crises; with the production of CO2 from fossil fuels predicted to continue dangerously damaging the environment for decades to come, while the fossil fuel energy sources themselves run out, alternatives are clearly needed to continue powering society. MOFs are introduced as potential materials which can fulfil both of these needs. Chapter 2 describes the synthesis of the H4LX series, which utilise the Suzuki-Miyaura cross-coupling reaction to generate a large quantity of a versatile ligand pre-cursor (3,5-di(p-carbethoxy)benzene boronic acid), which is then used to generate a large number of ligands via a further Suzuki-Miyaura cross-coupling reaction with a dihalogenated core. A green synthetic route to an analogous ligand to the first in the series (H4L1P, which differs from H4L1 by the replacement of two phenyl rings with pyridyls) is then described, which reduces the synthetic steps by 66% (2 steps instead of 6), and the cost by 95% (£0.51/g instead of £11.68/g). Chapter 3 describes the design, synthesis, and characterisation of a series of Cu(II) metal-organic frameworks (MFM-191 to 198), and their respective simulated isotherms, which enable rapid identification of promising frameworks for materials which theoretically approach and even exceed the American Department of Energy’s (DoE’s) target value for CH4 working capacity, and also potentially provide an alternative to current proposals for CO2 storage and shipping. The discussion on these frameworks is split into two studies: Exploration of the effects of interpenetration and classes thereof on low and high pressure gas sorption (MFM-191,192 and 193), and analysis of attempts to fine tune the high pressure uptake of a series of non-interpenetrated isoreticular structures via extension and functionalisation of the central core of the ligand (MFM-193 to 198). The first group of frameworks demonstrates how interpenetration aids low pressure uptake, but hinders maximum high pressure uptake. MFM-191 (which exhibits 2-fold interpenetration, class IIa) displays an uptake of CH4 of 1.97 wt% at 1 bar and 21.40 wt% and 80 bar, 298 K and an uptake of CO2 of 2.88 mmol/g at 1 bar, and 16.69 mmol/g at 30 bar, 298 K; while MFM-193 (a non-interpenetrated MOF with the same topology) demonstrates a greater difference between uptakes, with uptakes for CH4 of 0.85 wt% at 1 bar and 47.06 wt% for 80 bar, 298 K, and uptakes for CO2 of 0.65 mmol/g at 1 bar and 40.82 mmol/g at 30 bar, 298 K. This larger difference is due to the decreased host-guest interactions at low loadings, and works in favour of a better working capacity for CH4 for the non-interpenetrated framework. Alteration of the class of interpenetration (from class IIa to class Ia) results in overall uptake behaviour which lies between the two, displaying an uptake for MFM-192 of CH4 of 2.11 at 1 bar, and 31.36 wt% at 80 bar, 298 K and an uptake of 2.89 2.89 mmol/g at 1 bar and 24.07 mmol/g at 30 bar for CO2 at 298 K. The non-interpenetrated series of MOFs (MFM-193 to 198), shows how upon functionalisation of the central core of ligand H4L1, the gas sorption properties are increases in accordance to the aromaticity of the ligand, with an increase in maximum volumetric uptake (at 80 bar, 298 K) of CH4 from 233.29 to 251.89 cm3/cm3 from MFM-193 (with H4L1, a ligand with a phenyl ring as the central core) to MFM-195 (synthesised from H4LAN, a ligand with an anthracene moiety as its central core). Surprisingly, the amine-functionalised MOF (MFM-196) displays the lowest uptake of both CH4 and CO2 at high pressure compared to the other functionalised MOFs (MFM-194 and MFM-195) Extension of the ligand core from one phenyl ring to biphenyl and pyrene based ligands affords MFM-197 and MFM-198, which in turn display the highest theoretical gravimetric CH4 working capacities 5-80 bar (48.51 wt% and 44.15 wt% at 298 K, respectively). Furthermore, working capacities calculated from the 273 K simulated isotherms for MFM-198 (the pyrene functionalised framework) show that this MOF is capable of exceeding the DoE target for gravimetric working capacity of 50 wt% (and nearing the volumetric target of 264 cm3 cm-3), by delivering 52.3 wt% and 256.9 cm3 cm-3 between 5-80 bar. However, upon attempts to activate these Cu(II) frameworks, none were stable enough to obtain a permanent porosity, even from ‘soft’ activation methods such as supercritical CO2; therefore, new frameworks were sought which would be designed to have enhanced stability. Chapter 4 describes the synthesis of two Zr(IV) MOFs, synthesised from H4L1 and H4L1P (MFM-421 and MFM-422) designed to display enhanced stability over the Cu(II) MOF series, and allow acquisition of experimentally gathered high pressure data. This is particularly interesting for the MOF synthesised from H4L1P, as the green, cost-effective synthesis conditions of the ligand are potentially valuable for industrial applications. Both MOFs display an increase in stability over the Cu(II) series, with a measureable BET of 3,300 m2/g for MFM-421 and 2,500 m2/g for MFM-422. The high pressure CH4 and CO2 capacities of both frameworks were measured, and, while they were lower than the simulated Cu(II) series, they were highly competitive compared to published MOFs. MFM-421 is shown to have the fourth highest CH4 gravimetric working capacity at 298 K (compared to a list of the highest experimentally recorded MOFs for methane working capacity), and MFM-422 the sixth, measuring values of 25.7 wt% and 22.8 wt%, compared to the three highest of 31.0 wt%, 35.0 wt% and 42.3 wt% for MOF-177, MOF-205 and Al-soc-MOF-1, respectively. Importantly, compared to HKUST-1 (the only framework amongst this list that is cheaper than H4L1P to buy/synthesise), both of these frameworks exhibit higher gravimetric working capacities (which for HKUST-1 is 16.3 wt% at 298 K). The analysis of CO2 high pressure isotherms for potential in storage and shipping shows that these MOFs exhibit an increase in storage capacity at 298 K, 30 bar over capacity of a tank at the same conditions of over 500% for MFM-421 (7,708 mol/m3 compared to 1,458 mol/m3) and over 650% for MFM-422 (9,605 mol/m3). While the highest of these values still stands at only 43% of the value of a tank at 26.5 bar and 263 K, the ability to store this much CO2 at ambient temperatures allows more flexibility in route and less energy intensive storage conditions. Chapter 5 summarises the CH4 and CO2 storage properties of these structures and draws overall conclusions from the work.